THE CONSTITUTIONALIZATION OF THE PROCESS - Lorca Navarrete, Antonio María (2017)
The present article seeks to present the itinerary to follow in the relations between process and constitution. It is specified what is the method relative to the purpose pursued by procedural law with a view to the only reference that would legitimize it as the constitutional text. It also details the responsibility of procedural law and its constitutional commitment. Finally, it describes the substantivity of procedural law and the concept that advocates justice.